2022
DOI: 10.1177/13548565221104989
|View full text |Cite
|
Sign up to set email alerts
|

Tracing a historical development of conspiracy theory networks on the web: The hyperlink network of vaccine hesitancy on the Danish web 2006–2015

Abstract: This article investigates the vast field of conspiracy theories by focusing on the example of conspiracy theories related to vaccine hesitancy. Conspiracy theories have been with us for a long time, and as any other type of semantic content they spread by travelling through media. Therefore, if one wants to understand how conspiracy theories proliferate, it is relevant to investigate the media roads by which they travel and that each offer different opportunities for establishing connections. It is obvious tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…For instance, [ 13 ] investigate the transnational spread of political ideologies with the help of hyperlink networks. Likewise, researchers employ SNA methods to quantify structural network attributes and specify how hyperlink networks are employed to advocate political agendas [ 33 ], mobilize against certain religions [ 34 ] or how conspiracy theories develop over time on the web [ 14 ]. Furthermore, a conversion between hyperlink analysis and social media is provided by [ 35 ] who investigate how online connections among Korean politicians have developed from the Web 1.0 to the Web 2.0.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, [ 13 ] investigate the transnational spread of political ideologies with the help of hyperlink networks. Likewise, researchers employ SNA methods to quantify structural network attributes and specify how hyperlink networks are employed to advocate political agendas [ 33 ], mobilize against certain religions [ 34 ] or how conspiracy theories develop over time on the web [ 14 ]. Furthermore, a conversion between hyperlink analysis and social media is provided by [ 35 ] who investigate how online connections among Korean politicians have developed from the Web 1.0 to the Web 2.0.…”
Section: Related Workmentioning
confidence: 99%
“…Various studies have already attributed hyperlink networks the ability to capture real-world offline interactions between individuals or organizations [ 11 , 12 ]. Specifically in recent years hyperlink networks often found usage when analyzing the spread of political ideas [ 13 ] or conspiracy theories [ 14 ]. While [ 15 ] even observed that online hyperlink communities are based on their offline geospatial locations and further emphasized their role for improving industry performance.…”
Section: Introductionmentioning
confidence: 99%
“… Brügger’s (2022) study – ‘Tracing a Historical Development of Conspiracy Theory Networks on the Web: The Hyperlink Network of Vaccine Hesitancy on the Danish Web 2006–2015’ – showcases how studying the historical development of hyperlink networks can help researchers understand the proliferation of conspiracy theories. To illustrate this, the author chose the case of vaccination-related conspiratorial content on Danish websites.…”
Section: Outline Of Articlesmentioning
confidence: 99%
“…Following Heft and Buehling's (2022) methodological reflection, two empirical studies exemplify how the dissemination of conspiracy theory-related information can be studied across websites and across platforms. Brügger's (2022) study -'Tracing a Historical Development of Conspiracy Theory Networks on the Web: The Hyperlink Network of Vaccine Hesitancy on the Danish Web 2006-2015'showcases how studying the historical development of hyperlink networks can help researchers understand the proliferation of conspiracy theories. To illustrate this, the author chose the case of vaccination-related conspiratorial content on Danish websites.…”
Section: Diffusion Of Conspiracy Theories Onlinementioning
confidence: 99%
“…The phenomenon of vaccine hesitancy traces its origins back to the early stages of vaccination introduction and has garnered increased attention, particularly in light of the ongoing COVID-19 pandemic [ 21 ]. This concept encompasses a reluctance or hesitation to accept vaccines, despite readily accessible vaccination services [ 22 ]. The significance of this issue extends beyond individual choices, as vaccine hesitancy has the potential to undermine public health efforts, particularly in achieving the levels of immunity necessary for disease control and eradication at the population level.…”
Section: Introductionmentioning
confidence: 99%